2013
DOI: 10.1016/j.bmc.2013.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Novel 1H-imidazol-2-amine derivatives as potent and orally active vascular adhesion protein-1 (VAP-1) inhibitors for diabetic macular edema treatment

Abstract: Novel thiazole derivatives were synthesized and evaluated as vascular adhesion protein-1 (VAP-1) inhibitors. Although we previously identified a compound (2) with potent VAP-1 inhibitory activity in rats, the human activity was relatively weak. Here, to improve the human VAP-1 inhibitory activity of compound 2, we first evaluated the structure-activity relationships of guanidine bioisosteres as simple small molecules and identified a 1H-benzimidazol-2-amine (5) with potent activity compared to phenylguanidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…In this regard, both synthetic procedures were suitable for amide and ester formation and provided satisfactory yields (values between 60% and 74%). The synthetic steps are depicted in Scheme 1 [23,24].…”
Section: Chemistrymentioning
confidence: 99%
“…In this regard, both synthetic procedures were suitable for amide and ester formation and provided satisfactory yields (values between 60% and 74%). The synthetic steps are depicted in Scheme 1 [23,24].…”
Section: Chemistrymentioning
confidence: 99%
“…It has been reported that human serum CAOs cause angiopathy in diabetes (9). Therefore, various CAO inhibitors have been developed as therapeutic drugs (10,11).…”
mentioning
confidence: 99%
“…A complete uninterrupted enzyme inhibition is likely to be a challenge for the noncovalent/reversible inhibitors going forward, and higher or more frequent dosing to achieve this may reduce the therapeutic window. For example, an in vivo study using compound 7 (dosing daily at 10 mg/kg PO over 2 weeks) indicated that this inhibitor was not able to completely inhibit plasma SSAO/VAP-1 levels 24 h after the final dose (Inoue et al, 2013c), further supporting this critical pharmacokinetic/ pharmacodynamic relationship.…”
Section: Discussionmentioning
confidence: 99%